Evaluation of the possibility of chaos for doubly-fed induction generator in wind power generation system - Van, Co Nhu; Quang, Nguyen Phung; Hai, Nguyen Thanh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The doubly-fed induction generator (DFIG) has the advantages of compactness and low cost, so it has been applied more and more in practice. However, the structure of the DFIG system is complex, multivariable, nonlinear, and difficult to control. Chaos is a phenomenon that only occurs with nonlinear dynamical systems, sensitive to initial conditions and aperiodic but it is governed by deterministic laws, unlike random perturbations. For most powertrain systems, chaos causes disadvantages, reduce performance, and even destruction of the system. By method of analysis based on theory and simulation, the paper will demonstrate the chaotic phenomenon for DFIG when the parameters of the system change into a certain value. From that set of parameters, the controller is designed to avoid or eliminate that chaotic behavior, so that the system works more reliably and with better quality.